Loneliness and Nomophobia in Nursing Students - Siti Ainur Rohmawati; Mamnuah Mamnuah (Sarana Ilmu Indonesia (salnesia), 2026)
Nursing students often faced challenges in adapting socially to new environments, which can lead to feelings of loneliness. In response, many turn to excessive smartphone use, potentially resulting in nomophobia. This study aims to examine the relationship between loneliness and nomophobia among final-year nursing students who are studying away from home. The study employed a correlational design with a cross-sectional approach. A total sampling technique was used, involving 147 subjects. Data collection instruments included validated and reliable questionnaires: the UCLA Loneliness Scale (ULS-20) to assess loneliness, and the Indonesian version of the NMP-Q-10 to measure nomophobia. Data were analyzed using the Spearman rank correlation test. The results showed no significant relationship between loneliness and nomophobia among the subjects (p = 0,621; p > 0,05). Future studies are expected to use longitudinal designs and more complex conceptual models to gain a deeper understanding of the mechanisms underlying this relationship. The researchers recommend that nomophobia studies be conducted offline and linked to other aspects such as length of time spent away from home, frequency of returning home, and intensity of smartphone use.